2021
DOI: 10.3390/medicina57111211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iodine and Selenium Nutritional Status in Women of Reproductive Age in Latvia

Abstract: Background and Objectives: Adequate dietary intake of iodine and selenium is essential during pregnancy. While iodine is vital for maternal thyroid function and fetal development, selenium contributes to the regulation of thyroid function and thyroid autoimmunity. This study aimed to assess the consumption of iodine- and selenium-containing products by women of reproductive age and the iodine and selenium nutritional status of pregnant women in Latvia. Materials and Methods: Population health survey (2010–2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Supplementation with 60 μg/day of selenomethionine is recommended for healthy women and even 200 μg/day for women at risk of thyroid postpartum disturbances, although these amounts are normally not provided by a common prenatal trace element preparation [ 46 ]. Similar to our observations have been reported from a study conducted in Latvia where, despite the usage of a broad supplement (70%), pregnant females failed to achieve the optimal Se status [ 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Supplementation with 60 μg/day of selenomethionine is recommended for healthy women and even 200 μg/day for women at risk of thyroid postpartum disturbances, although these amounts are normally not provided by a common prenatal trace element preparation [ 46 ]. Similar to our observations have been reported from a study conducted in Latvia where, despite the usage of a broad supplement (70%), pregnant females failed to achieve the optimal Se status [ 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of Se in blood plasma was evaluated using the fluorometric method with di-amino-naphthalene and acidic hydrolysis. The measurement of Sepp1 was carried out using the previously reported Human Sepp1 ELISA kit [ 25 ]. Chemicals were produced by Sigma-Aldrich (Spruce St., Saint Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Another study completed in Turkey measured newborn UIC and found 51% of newborns were I deficient [ 75 ]. Finally, studies of Swedish women ( n = 604) [ 76 ], Cyprian women ( n = 128) [ 77 ], and Latvian women ( n = 129) [ 78 ] report UICs of 113 μg/L, 105 μg/L, and 147 μg/L, respectively, suggesting mild-to-moderate I insufficiency may occur in these countries.…”
Section: Iodine and Thyroid Function In Pregnancymentioning
confidence: 99%
“… Veisa et al. [ 78 ] Observational Latvia Mild-to-moderate iodine deficient population N/A Maternal median UIC 147 μg/L. Naess et al.…”
Section: Iodine and Offspring Neurodevelopmentmentioning
confidence: 99%